Information Barriers in Global Markets: Evidence from International Subcontracting Relationships - Massa, Massimo; Schumacher, David (Journal of Financial and Quantitative Analysis, 2020)
We study the link between information barriers in global markets and the organizational form of asset management. Fund families outsource funds in which they are at an informational disadvantage to generate performance. Using a structural model of self-selection, we endogenize the outsourcing decision and estimate positive gains from outsourcing of 4–14 basis points per month, thereby reconciling underperformance of outsourced funds with performance maximization by fund families. The gains from outsourcing provide a novel proxy for the information barriers that segment global financial markets: The more segmented the underlying markets where the funds invest, the larger the gains from outsourcing.